(untitled) (Homiletic, 2011)
This essay argues that current forms of sermon evaluation tend to reinforce preaching as a singular event of the isolated preacher, rather than as a communal, dialogical, and formational practice of the church. Our perception of preaching and tools for evaluation need to be revised in order for sermon evaluation to align with this emerging understanding of preaching as a church practice.